ESSAYS ZU GEORGE ENESCU - GEORGESCU, Corneliu Dan (Studia Universitatis Babes-Bolyai Musica, 2008)
The names of Enescu, Bartók and Strawinsky are frequently associated, and some points of view concerning the consideration of the traditional national music seam to be similar. Nevertheless is their evolution quite different. Enescu will be soon relatively isolated from international musical avant-garde, and he has spent much more time and energy as interpret and cultural organizator of the musical life of his homeland. His tendency to an European synthesis with some elements of Romanian lautari-folclore seams to ground to him on a most conservative conception. He is less successful as composer and his deep originality is difficult to analyze and accept. Carl Gustav Jung defines about 1912-1919 the notion of the archetypes of collective unconsciousness (like Animus-Anima, Persona-Ombra) as an universal a priori element, which may constantly change his form. An application to the music suggests the use of some “musical archetypes” (like Initium-Centrum-Finis, Crescere-Planum-Descrescere, Culmen-Vallis, Maximum-Minimum) and may reveal some common gestures of all composers, but also some specific details. Six works of the late period by Enescu are experimentally analyzed in this respect. An attempt to precisely define the "musical time" by Enescu, frequently evoqued in recent studies, would also contribute to understand one of the most specific and intimates zones of his creation. The first problem in this approach is the formulation of some analytical criteria and an adequate terminology, as the domain is usually quite fuzzy defined. The answer to such question cannot be simple - as in the most cases of the attempts to describe the Ineffable of Enescu.